Design of cyclic prefix characteristic-based OFDM system for WiMAX technology - Das, Bhagwan; Abdullah, Mohammad Faiz Liew; Mohammed Ahmed, Adeb Ali; Shaikh, Muhammad Mujtaba (Springer, 2019)
Worldwide interoperability for microwave access (WiMAX) offers the wireless connectivity using orthogonal frequency division multiplexing (OFDM) modulation is a proficient wireless technology that capacities high-speed data transmission facilities. The existing WiMAX techniques have the problem of increase in inter-symbol interference (ISI) and bit error rate (BER) at reduced power spectrum that degrades the performance of WiMAX system due to high data rate transmission. The utilization of different adaptive modulation techniques seen as a potential solution to reduce the ISI and BER for high data rate transmission. In this paper, OFDM is adapted using advanced modulation technique for WiMAX system. The technique proposes the cyclic prefix (CP) is utilized that include supplementary bits at the stage of the transmitter. The proposed technique offers minimization of ISI and improvement in BER. It is defined that performance of the existing CP system is equated with the designed single cyclic prefix (SCP) and double cyclic prefix (DCP) and non-cyclic prefix (NCP). BER, probability of error, and power spectral density are utilized to analyse the performance of the designed system. The OFDM based SCP and DCP and NCP for WiMAX are demonstrated for modulation techniques such as; QPSK, BPSK, and QAM. It is determined that BPSK has the smallest BER when compared to QPSK, 16-QAM, and 64-QAM modulations. It is also demonstrated that QPSK is also very competent, however, it has a higher BER as compared to BPSK modulation. It is also observed that 16-QAM and 64-QAM are less efficient in terms of BER compared to QPSK and BPKS modulations. 64-QAM offers the high data rates, and due to high SNR ratio. The designed system is tested for under AWGN and Rayleigh fading channel, and effect power spectral density of signal to noise ratio on OFDM for rayleigh fading channel are demonstrated for SCP and DCP and NCP. It is determined that the OFDM transmitter with proposed DCP for random signals is efficiently reducing the BER and ISI for WiMAX system.